Role of Vitamin D on IL-6 In Type 2 Diabetes Mellitus: Literature Review - Ni Kanaya; Hanna Gabriella Sarumaha; Syaraufa Zahra Nuraqilla; Grace Keren; Teddy Tjahyanto (Green Publisher Indonesia, 2022)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels, insufficient insulin secretion by pancreatic cells, insulin resistance, and inadequate insulin secretory compensatory response. Various reports have shown that low-grade chronic inflammation is associated with the risk of developing T2DM. In recent years, studies have suggested that increased concentrations of circulating inflammatory markers, such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and high-sensitivity C-reactive protein (hs-CRP) have been reported may increase the incidence of T2DM. Recently it has been found that vitamin D plays a role not only in bone remodeling, but as an immunomodulator. Administration of vitamin D therapy suppresses the proliferation of T cells and monocytes and downregulates proinflammatory cytokines including CRP, TNF-α, Interleukin-1, 6, 8, and increases the production of the anti-inflammatory cytokine IL-10. A literature review was carried out to collect the latest results from several studies regarding the role of vitamin D on IL-6 in type 2 diabetes mellitus. The literature sources were taken from journal articles published online in the period 2017-2021. The databases used are MDPI, PubMed, ScienceDirect, Wiley, and Hindawi. The results of the literature review show various findings. Several studies showed a significant difference and no significant difference in IL-6 after vitamin D administration clinically or statistically. Additional studies are needed to specifically examine the optimal dose of vitamin D to reduce IL-6-mediated inflammation in T2DM, determine the best dose between calcemic and immunomodulating effects, and the role of vitamin D in inflammation so that it can be an effective adjunct therapy in the treatment of T2DM.